A review of the genus Caissa Hering in China (Lepidoptera: Limacodidae) - Wu, Chunsheng; Fang, Chenglai (Zootaxa, 2008)
Four species of the genus Caissa Hering are recognized from China, in which C. longisaccula and C. caii are described as new to science and C. parenti Orhant is reported for the first time in China. The photographs of moths and their genitalia are given. A key to the Chinese species of the genus is provided.